2002
DOI: 10.1079/bjn2002631
|View full text |Cite
|
Sign up to set email alerts
|

A review of the role of the gut microflora in irritable bowel syndrome and the effects of probiotics

Abstract: Irritable bowel syndrome (IBS) is a multi-factorial gastrointestinal condition affecting 8 -22 % of the population with a higher prevalence in women and accounting for 20 -50 % of referrals to gastroenterology clinics. It is characterised by abdominal pain, excessive flatus, variable bowel habit and abdominal bloating for which there is no evidence of detectable organic disease. Suggested aetiologies include gut motility and psychological disorders, psychophysiological phenomena and colonic malfermentation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 38 publications
1
95
0
Order By: Relevance
“…The differences in faecal bacterial population between IBS and control subjects have been reported in several studies (Balsari et al, 1982;Bradley et al, 1987;Madden & Hunter, 2002;Mättö et al, 2005). We found a marked difference in the proportions of the C. coccoides-E. rectale group of clostridia between constipation-type IBS subjects and control subjects.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The differences in faecal bacterial population between IBS and control subjects have been reported in several studies (Balsari et al, 1982;Bradley et al, 1987;Madden & Hunter, 2002;Mättö et al, 2005). We found a marked difference in the proportions of the C. coccoides-E. rectale group of clostridia between constipation-type IBS subjects and control subjects.…”
Section: Discussionmentioning
confidence: 93%
“…The existence of abnormal colonic fermentation in IBS (King et al, 1998) and alleviation of IBS symptoms by eradication of small intestinal bacterial overgrowth by antibiotic therapy (Pimentel et al, 2000), suggest that the intestinal microbiota has a role in IBS. Some studies have reported differences in the faecal bacterial population between IBS and control subjects (Balsari et al, 1982;Bradley et al, 1987;Madden & Hunter, 2002;Mättö et al, 2005;Malinen et al, 2005). However, the results obtained in earlier studies are partly contradictory, and with the exception of those of Mättö et al (2005) and Malinen et al (2005), are based on the culture-based analysis of the microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IBD is a collection of disorders including ulcerative colitis, Crohn's disease and pouchitis, characterized by chronic or recurrent inflammation, ulceration and abnormal narrowing of the GIT resulting in abdominal pain, diarrhoea and gastrointestinal bleeding (Hanauer, 2006;Marteau et al, 2001). IBS is typically characterized by abdominal pain, excessive flatus, variable bowel habit and bloating (Madden & Hunter, 2002). Several studies have been conducted to investigate the efficacy of probiotics in treatment of IBD (Guandalini, 2002;Ma et al, 2004;Zhang et al, 2005).…”
Section: Therapeutic Benefitsmentioning
confidence: 99%
“…However, the relevance of these data has been questioned for both the low reliability of the test, the weak clinical response to antibiotic therapy and the low placebo effect compared to other IBS studies [41] . However, there is general agreement that at least in a proportion of patients with IBS and bloating [42][43][44] an increased bacterial fermentation can contribute to the symptoms [45] . The net effect of colonic microflora on gas metabolism depends on the balance between gas-producing and gas-consuming microorganisms, which varies considerably among individuals [46] .…”
Section: Increased Luminal Contentsmentioning
confidence: 99%